Pengaruh Tingkat Pendidikan, Tenaga Kerja, Investasi dan Ekspor Terhadap Pertumbuhan Ekonomi di Indonesia - Pratiwi, Ida Ayu Candra (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
This study aims to analyze the effect of the level of education, labor, investment and exports simultaneously and partially on economic growth in Indonesia. As well as to analyze the variables between the level of education, labor, investment and exports which have a dominant influence on economic growth in Indonesia for the 2015-2019 period. The types of data used in this research are quantitative data and qualitative data. In this study, the data used are secondary data obtained from the Central Statistics Agency (BPS). This research was conducted in all provinces in Indonesia. The data analysis technique used in this study is multiple linear regression analysis. The results showed that the level of education, labor, investment, and exports simultaneously affected economic growth in Indonesia. The level of education, labor, investment, and exports partially affects economic growth in Indonesia. As well as the investment variable is the variable that has the most dominant influence on economic growth in Indonesia in the 2015-2019 period.